Analisa Kegagalan Upaya Perdamaian Turki Dengan Partiya Karkeren Kurdistan (PKK) Tahun 2009-2015 - Sheila Rosi Andika; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The prolonged separatist conflict that the Partiya Karkeren Kurdistan (PKK) had with the Turkish government was caused by the failure of peace efforts between the two sides, hence raising questions about what caused the failure of the peace effort. Therefore, this article aims to analyze the factors behind the failure of peace efforts between Turkey and the PKK that occurred in 2009-2015. Using Charles Kupchan’s stable peace theory. The article argued that the failure of the peace effort was due to Turkey’s and the PKK’s lack of compliance with Kupchan’s stable peace criteria and conditions, as well as the failure of the peace process at the unilateral accommodation stage as both sides did not trust each other’s commitments. Turkey assumed that if it continued the negotiation process, the PKK would increase their demands. Meanwhile, PKK assumed that the Turkish government was not serious about dealing with the Kurdish Question so that the peace effort was deadlocked.